932. Universal Hepatitis C Virus Screening in a Tennessee Tertiary Care Emergency Department. (26th November 2018) - Chastain, Cody A; Johnson, Jakea; Miller, Karen; Moore, Katie; Lako, Amanda; Zuckerman, Autumn; Han, Jin H; Self, Wesley H
Abstract: Background: Despite hepatitis C virus (HCV) age cohort and risk factor screening recommendations, many at-risk individuals remain undiagnosed. Current screening practices may not adequately capture those at high risk for infection, especially in regions with increasing injection drug use (IDU). Universal HCV screening in a Tennessee tertiary care emergency department (ED) was introduced to help define regional epidemiology and to improve diagnosis and linkage to care. Methods: This screening program was implemented in the Vanderbilt University Medical Center ED. Adult patients who underwent phlebotomy for clinical purposes were offered HCV screening. Samples were initially tested for HCV antibodies; if positive, samples were reflexed for HCV RNA testing. Patients with positive HCV RNA tests (i.e., active HCV infection) were notified, counseled, and offered linkage to care. Results: A total of 11, 637 screening tests were performed between April 1, 2017 and March 31, 2018, with 1, 008 (8.7%) HCV antibody positive and 488 (4.2%) RNA positive. Of note, 81 (0.7%) were HCV antibody positive but RNA testing could not be performed due to insufficient sample volume. Several notable populations had high rates of HCV (Table 1). Importantly, 3.9% of people not born between 1945 and 1965 were HCV RNA positive, and they were the majority (63.5%) of patients with active HCV (Table 2). A minority (31.6%) of those with active HCV had a known history of IDU (Table 2). Conclusion: HCV is common among patients presenting for emergency care at a Tennessee tertiary care ED. Universal screening identified many infections that would have been missed using age cohort and risk factors alone. ED HCV screening may be a useful method to augment guideline-based testing and intervene among populations not consistently screened. Disclosures: C. A. Chastain, Gilead Sciences, Inc.: Grant Investigator and Research Contractor, Grant recipient and Research support. J. Johnson, Gilead Sciences, Inc.: Grant Investigator, Grant recipient. K. Miller, Gilead Sciences, Inc.: Grant Investigator, Grant recipient. J. H. Han, Gilead Sciences, Inc.: Grant Investigator, Grant recipient. W. H. Self, Gilead Sciences, Inc.: Grant Investigator, Grant recipient.